Criminological analysis of the state and particularities of determination of the illegal possession of vehicles in Ukraine under conditions of armed aggression (Law and Safety, 2023)
The article deals with the criminological analysis of the state and peculiarities of determination of the illegal possession of vehicles in conditions of armed aggression. It has been established that the dynamics of illegal vehicle possession in the context of armed conflict are unfavourable. There has been a significant increase in the number of criminal offences committed under article 289 of the Criminal Code of Ukraine. It has been established that the deterioration of criminogenic situation according to the criterion under study was due to the intensification of a number of factors, the leading place among which is occupied by situational factors. Four groups have been defined and described, which are identified with the components of criminogenic situations.Supervisory and deficit factors are a group of determinants of illegal vehicle possession that represent complex criminogenic situations, the characteristics of which are inadequate control, supervision of vehicles in a static location. In situations of armed conflict, these determinants are shaped by the urgency of leaving vehicles unattended, prioritising saving lives and health, personal freedom when there is a risk of combat exposure, and the occupation of territory.Criminal and combat factors of illegal possession of vehicles are formed as an element of the combat situation; possession of vehicles by civilians occurs either on the battlefield or in connection with the performance by representatives of the aggressor country (combatants and other participants in the armed conflict) of tasks harmful to the interests of Ukraine: illegal possession of vehicles by members of diversionary-intelligence groups or hostile (Russian) combatants during combat operations.Occupation factors are most intensively reproduced in the conditions of full-scale armed aggression of the Russian Federation against Ukraine and are associated with the same large-scale and complex victimisation of the population who find themselves in the temporarily occupied territories. This category of citizens is completely deprived of legal guarantees of their rights and freedoms.Victim-urban factors are represented by a conglomeration of circumstances of criminogenic significance that form a situation of relaxed control over vehicles in places where they are forced to concentrate, for relatively long periods of time. These situations primarily involve the illegal possession of vehicles by internally displaced persons. The mass displacement of citizens from the northern, eastern and southern regions of Ukraine to the western region has created a shortage of secure, properly equipped parking spaces, making it easier for criminals to gain access to vehicles.
Keywords: aggression; armed conflict; occupation; criminality; illegal possession of vehicles; road safety.